Об’єктивна обумовленість єдності та диференціації правового регулювання захисту трудових прав суддів - Акуленко, В. В.; Akulenko, V. V. (Науковий вісник публічного та приватного права. - 2023. - Вип. 6. - С. 45-50, 2023)
Відзначено, що єдність та диференціація правового регулювання захисту трудових прав суддів є об’єктивно обмовленим явищем, що пояснюється наступним: по-перше, вказаний принцип забезпечує здійснення захисту трудових прав суддів на рівні, не нижчому у порівнянні з іншими працівниками; по-друге, дозволяє створити такі умови для захисту трудових прав суддів, які будуть відповідати суспільно важливій значимості їх службово-трудової діяльності. Виділено наступні особливості правового статусу судді як суб’єкта трудового права: по-перше, наявність особливих вимог до трудової правосуб’єктності осіб, які бажають набути статусу судді; по-друге, судді володіють більш широким колом службово-трудових прав та юридичних обов’язків у порівнянні з іншими категоріями працівників; по-третє, фактично, роботодавцем у трудових правовідносинах із суддями є держава; по-четверте, окрім базових економічних та соціальних гарантій, на суддів поширюють додаткові, зокрема політичні, гарантії в процесі здійснення трудової діяльності.

The relevance of the article lies in the fact that the legal regulation of the protection of the labor rights of judges is built on a system of starting points, initial ideas, which are commonly called principles. The system of relevant principles is quite broad and covers a wide range of principles, each of which plays an important role in ensuring the effective functioning of social relations that arise in the context of regulating the protection of the labor rights of judges. However, it should be noted that unity and differentiation play a key role in the system of these principles. The importance of the existence of this principle is due to the fact that it is with its help that the Ukrainian legislator has the opportunity to take into account the specifics of the labor activity of judges by creating such labor legislation that fully takes into account the specifics and peculiarities of the legal status of judges, which in turn will make it possible to more effectively protect their rights as subjects of labor law. The article, based on the analysis of the scientific views of scientists and the norms of the current legislation, singles out the factors that objectively determine the need for unity and differentiation of the legal regulation of the protection of the labor rights of judges. It was noted that the unity and differentiation of the legal regulation of the protection of the labor rights of judges is an objectively discussed phenomenon, which is explained as follows: first, the specified principle ensures the protection of the labor rights of judges at a level not lower than that of other employees; secondly, it allows creating such conditions for the protection of the labor rights of judges that will correspond to the socially important importance of their official and labor activities. The following features of the legal status of a judge as a subject of labor law are highlighted: firstly, the presence of special requirements for the labor legal personality of persons who wish to acquire the status of a judge; secondly, judges have a wider range of official and labor rights and legal obligations compared to other categories of employees; thirdly, in fact, the employer in labor relations with judges is the state; fourthly, in addition to basic economic and social guarantees, judges are subject to additional, in particular, political guarantees in the course of their work.

Отмечено, что единство и дифференциация правового регулирования защиты трудовых прав судей является объективно оговоренным явлением, что объясняется следующим: во-первых, указанный принцип обеспечивает защиту трудовых прав судей на уровне, не ниже по сравнению с другими работниками; во-вторых, позволяет создать такие условия для защиты трудовых прав судей, которые будут соответствовать общественно важной значимости их служебно-трудовой деятельности. Выделены следующие особенности правового статуса судьи как субъекта трудового права: во-первых, наличие особых требований к трудовой правосубъектности лиц, желающих приобрести статус судьи; во-вторых, судьи обладают более широким кругом служебно- трудовых прав и юридических обязанностей по сравнению с другими категориями работников; в-третьих, фактически работодателем в трудовых правоотношениях с судьями является государство; в-четвертых, кроме базовых экономических и социальных гарантий, на судей распространяют дополнительные, в частности, политические гарантии в процессе осуществления трудовой деятельности.
Objective conditioning of the unity and differentiation of the legal regulation of the protection of the labor rights of judges
Keywords: об’єктивна обумовленість; єдність; диференціація; правове регулювання; захист; трудові права; судді; objective conditioning; unity; differentiation; legal regulation; protection; labor rights; judges; объективная обусловленность; единство; дифференциация; правовое регулирование; защита; трудовые права; судьи